SMEs Culinary Purchase Decisions Determine by Brand Image, Price and Product Uniqueness - Hikmat Maulana, Lucky (Publisher Cv. Inara, 2023)
The development of the culinary business is increasingly rapid, marked by the emergence of many increasingly varied food sellers. Many SMEs in the culinary business take advantage of practicality in consuming food and drinks. This research aims to determine consumer perceptions and the influence of brand image, price, and product uniqueness factors on purchasing decisions for SMEs products simultaneously or partially. The population and sample are 120 consumers taken by nonprobability sampling technique. The analytical method used in this research is descriptive and verification. The instrument test was carried out with validity and reliability. Research data analysis includes multiple linear regression analysis, multiple correlation analysis, and hypothesis testing. The research results show that simultaneously and partially the factors of brand image, price, and product uniqueness have a positive and significant effect on purchasing decisions.